Femtosecond excited state dynamics of a stilbene–viologen charge transfer complex assembled via host–guest interaction. Issue 12 (8th November 2017) - Rusalov, Mikhail V.; Volchkov, Valery V.; Ivanov, Vladimir L.; Melnikov, Mikhail Ya.; Shelaev, Ivan V.; Gostev, Fedor E.; Nadtochenko, Victor A.; Vedernikov, Artem I.; Gromov, Sergey P.; Alfimov, Michael V.
Abstract : The ultrafast photoinduced electron transfer in a supramolecular charge transfer complex was studied. Abstract : The dynamics of the excited states of a supramolecular complex with a charge transfer between ( E )-bis(18-crown-6)stilbene and 4, 4′-( E )-ethene-1, 2-diylbis[1-(2-ammonioethyl)pyridinium]tetraperchlorate was studied by means of femtosecond transient spectroscopy. It is found that the characteristic time of the conversion of the locally excited (LE) state into the charge transfer (CT) state is equal to 300 fs, whereas the characteristic time of the conversion of the CT state into the ground state is equal to 400 fs. Due to host–guest interaction involving hydrogen bonds, the complex possesses high thermodynamic stability. As a result of ultrafast photoinduced processes of the direct and back electron transfer, the complex does not fluoresce. Upon the interaction of the complex with alkaline-earth metal cations, "switch-on" of its fluorescence occurs.